(untitled) (Comprehensive Journal of Science, 2025)
In the present investigation, Intra-and inter-specific variations in morphometric indices of 450Mullussermuletusand411Mullus barbatus, from Mediterranean Sea at Benghzi, were revealed during the period from January to December 2022.The type of allometry of morphometric measurements showed that for both species studied, males showed isometric measurements more than females for both studied species. Meristic characters are significantly different between the two species studied. No sexual dimorphism was found in the meristic characters of the two species under study.The fish Mullussermuletusmeasured between 11.5 to 18.9 cm in length for 189 males and 12.5 to 19.9 cm for 261 females. Their weights ranged from 18.43 to 79.42 grams for males b = 3.054 and 20.14 to 99.02 grams for females b = 2.887. The fish, Mullus barbatus, ranged in length from 10.5 to 17.9 cm for 185 males and from 11.5 to 18.9 cm for 226 females. Males weighed between 24.34 and 112.42 grams (b = 3.029), while females weighed between 18.04 and 83.02 grams (b = 2.856). Features like the overall amount of rakers on the gill, rays number in dorsal, pectoral, and caudal fins were counted. The results showed no differences in these features between males and females of two target speciesfrom the Benghazi coast in the Mediterranean Sea, eastern Libya.